SAT0358 Decreased body fat, lean body mass and bone mineral density in patients with systemic sclerosis are associated with disease activity and physical activity. (15th June 2017) - Oreska, S; Spiritovic, M; Cesak, P; Cesak, M; Storkanova, H; Kubinova, K; Klein, M; Vernerova, L; Ruzickova, O; Mann, H; Pavelka, K; Senolt, L; et al.
Abstract : Background: Systemic sclerosis (SSc) is characterized by fibrosis of the skin and visceral organs, especially digestive tract, and musculoskeletal involvement, which limit mobility/self-sufficiency of patients, and can have a negative impact on body composition. Objectives: To assess body composition and physical activity of SSc patients and healthy controls (HC). Methods: 59 patients with SSc (50 females, 9 males; mean age 52.1; disease duration 6.7 years; limited cutaneous (lcSSc, 36)/diffuse cutaneous (dcSSc, 23)) and 36 age-/sex-matched HC (30 females, 6 males, mean age 51.4) without rheumatic/tumor diseases or manifest cardiovascular event were included. SSc patients fulfilled EULAR/ACR 2013 criteria. Anthropometric parameters and body composition were assessed (by densitometry-iDXA Lunar, and by bioelectric impedance-BIA-2000-M), and physical activity was evaluated using Human Activity Profile (HAP) questionnaire. Routine biochemistry analysis was performed after 8 hours of fasting. Disease activity was evaluated by EUSTAR SSc activity score. Data are presented as mean±SD. Results: Compared to HC, patients with SSc had significantly lower body-mass index (BMI: 26.4±3.3 vs. 22.4±4.3 kg/m 2, p<0.0001) and body fat % assessed by both iDXA (BF%: 37.2±6.6 vs. 32.6±8.2%, p=0.0014) and BIA (BF%: 31.1±6.4 vs. 24.6±7.8%, p<0.0001), and a trend to decreased visceral fat weight (0.9±0.9 vs. 0.5±0.5kg, p=0.0670). Compared to HC, SSc patients demonstrated significantly decreased lean body mass assessed by both iDXA (LBM: 46.6±7.5 vs. 40.9±6.8kg, p=0.0003) and BIA (LBM: 53.2±8.7 vs. 47.7±7.0kg, p=0.0017), and increased ECM/BCM ratio (extracellular mass/body cell mass: 1.03±0.1 vs. 1.29±0.4, p<0.0001), which reflects worse muscle predispositions for physical exercise, aerobic fitness/performance, and usually increases with deteriorating nutritional status. Compared to HC, SSc patients had significantly lower bone mineral density (BMD: 1.16±0.10 vs. 1.05±0.11g/cm 2, p<0.0001), and were currently able to perform less energetically demanding physical activities according to HAP score (84.7±6.6 vs. 64.1±17.2, p<0.0001). Disease activity negatively correlated with BF% (r=-0.324, p=0.014), and physical activity (HAP) positively correlated with BMD (r=0.276, p=0.034) and negatively with ECM/BCM (r=-0.625, p<0.0001). Conclusions: Compared to healthy age-/sex-matched individuals we found significant negative changes in body composition of our SSc patients, which are associated with their disease activity and physical activity, and could reflect their nutritional status, and gastrointestinal and musculoskeletal involvement. Acknowledgements: Supported by AZV-16–33574A, GAUK-214615. Disclosure of Interest: None declared